Improved Lifetime of Na-Ion Batteries With a Water-Scavenging Electrolyte Additive - Chen, Lin; Kishore, Brij; Song, Tengfei; Walker, Marc; Dancer, Claire; Kendrick, Emma (Frontiers in Energy Research, 2022)
The lifetime of sodium-ion batteries is strongly affected by degradation species and contaminants such as, H2O and HF, which are produced during formation and cycling. In this work the use of low levels of N,N-Diethyltrimethylsilylamine (DETMSA), as an electrolyte additive, shows an improvement in the stability and cycle life of a hard carbon vs layered oxide sodium-ion battery. Approximately 80% of the capacity is retained after 500 cycles, which is almost double the performance of the standard electrolyte. The additive works by reducing the surface ageing constituents as observed through XPS of the surfaces and the change in resistance after cycling. DETMSA is slowly consumed over time, however the extensive improvement in cycle life shows that low level of impurities and degradation species have a big impact upon cycle life.